Location of the mandibular incisal canal regarding to the root apices: a cone-beam computed tomography study - Z. S. Khabadze; M. M. Shubitidze; Sh. M. Solimanov; A. O. Kuznetsova; O. I. Magomedov; M. D. Abazyan; N. M. Kakabadze (LLC "Endo Press", 2020)
Relevance of the research topic. The mandibular incisive nerve provides innervation to the mandibular anterior teeth and its damage can lead to neurological and pain symptoms. There is a possibility of damage to this nerve during endodontic treatment in the anterior mandible.The aim is to study the location of the mandibular incisive canal relative to the root apices in the anterior mandible with cone-beam computer tomography (CBCT) scans.Materials and methods. We selected and measured from the tops of the roots of the teeth to the mandibular incisive canal in 180 CBCT-scans of patients aged from 24 to 80 years (90 men and 90 women; average age 53.27 ± 6.8) on sagittal view.Results. The average distance for all measurements from the mandibular incisive canal to the root apices was 7.2 ± 2.4 mm. The lowest distance was noted in the first premolar region on the left (1.4 mm), and the greatest the canine region on the same side (15.1 mm). There were no statistically significant differences between age and gender, between the sides, as well as in the area of different groups of teeth.Conclusion. Despite the fact that the risk of damage to this structure is quite small, it still exists and clinicians should not ignore this feature.